A Survey of Knowledge and Barriers of Healthcare Professionals toward Opioid Analgesics in Cancer Pain Management. (12th April 2022) - Ayoub, Nehad M.; Jibreel, Malak; Nuseir, Khawla; Al-Taani, Ghaith M.
Abstract : Purpose . Pain is among the most frequent and troubling symptoms in cancer patients. Despite the availability of updated treatment guidelines and effective pharmacological therapies, undertreatment of cancer pain remains a global problem. Opioids are the mainstay analgesics to treat moderate-to-severe cancer pain. The goal of this study was to assess the knowledge and barriers towards opioid analgesics for cancer pain management among healthcare professionals in Oncology Units in Jordan. Methods . A structured questionnaire was administered to healthcare professionals (consultant doctors, resident doctors, pharmacists, and nurses) at three Oncology Units in a cross-sectional study design. Results . A total of 201 healthcare professionals completed the questionnaire. The average age was 34.8 ± 8.1 years (range 23–58) and 49.3% of respondents were nurses. The mean score for the knowledge of opioids was 12.5 ± 3.2 out of 24 points (range 2–20). An acceptable level of knowledge was observed in 50.7% of participants, while 49.3% had poor knowledge. Knowledge items mostly answered incorrectly were related to opioid administration, pharmacology, dosing, adverse events, rotation, and toxicity. Knowledge scores were significantly higher for consultant doctors compared to pharmacists and nurses (p = 0.016 and p < 0.001, respectively). Healthcare professionals who handled opioid analgesics had significantly higher mean knowledge scores than those who did not (p = 0.012 ). Linear regression analysis revealed that being a consultant physician has an independent, statistically significant association with higher knowledge scores. Among perceived barriers to using opioids, fear of addiction by patients was the most frequently reported barrier by respondents (79.6%). Other highly recognized barriers were fear of adverse effects by patients (67.2%) and lack of training programs on opioid dosing and monitoring (63.7%). Conclusions . This study revealed major gaps in the knowledge of opioids and pain management among healthcare professionals. There is an urgent need for developing innovative interventions to improve the knowledge of opioid analgesics and the understanding of pain management guidelines among healthcare professionals in Jordan.